Personal Hygiene Reduces the Risk of Soil-Transmitted Helminth Worm Infection - Dicky Endrian Kurniawan; Enggal Hadi Kurniyawan; Muchamad Ferdy Rivaldi; Rizki Yahya Fahrezi; Safira Risqi Aprianti; Alfid Tri Afandi; Kholid Rosyidi Muhammad Nur (Health and Technology Journal (HTechJ), 2023)
Vegetable farmers risk being infected with Soil Transmitted Helminth (STH) due to frequent direct contact with soil contaminated by STH eggs. Worm infections transmitted through the soil cause disturbances in the tissues and organs of the body by taking nutrients from the vegetable growers' bodies, which can cause serious complications. The search process was carried out using a literature review using four databases, namely Google Scholar, Science Direct, WorldCat, and PubMed, with a publication range of 2018-2023. From all search results, ten articles match the research criteria. The results showed that vegetable farmers who have good personal hygiene can reduce the risk of STH infection. The presence of health workers here is expected to enable them to carry out health promotion, health education, and outreach to the community, especially to vegetable farmers, regarding good personal hygiene to prevent STH transmission.